Mutagenic activity promoted by amentoflavone and methanolic extract of Byrsonima crassa Niedenzu - Primila Cardoso, Cassia Regina; Mara de Syllos Colus, Ilce; Bernardi, Caroline Cristiane; Sannomiya, Miriam; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2006)
Byrsonima crassa is a plant pertaining to the Brazilian central savannah-like belt of vegetation and popularly used for the treatment of gastric dysfunctions and diarrhoea. The methanol extract contains catechin, tannins, terpenes and flavonoids; both mutagenic potential and antioxidant properties have been ascribed to flavonoids. The mutagenicity of some flavonoids is believed to be associated with the formation of reactive oxygen species and seems to depend on the number and position of hydroxyl groups. In the present study the mutagenic activity of the methanol, chloroform and 80% aqueous methanol extracts, as well as acetate and aqueous sub-fractions, of this medicinal plant were evaluated by Salmonella typhimurium assay, using strains 100, TA98, TA102 and TA97a, and in mouse reticulocytes. The results showed mutagenic activity of the methanolic extract in the TA98 strain without S9, but no mutagenicity to mouse cells in any of the extracts. The acetate fraction showed strong signs of mutagenicity without S9, suggesting that in this enriched fraction were concentrated the compounds that induced mutagenic activity. The aqueous fraction showed no mutagenic activity. The TLC and HSCCC analyses of the acetate fraction with some standard compounds permitted the isolation of the quercetin-3-O-beta-D-galactopyranoside, quercetin-3-O-alpha-L-arabinopyranoside, amentoflavone, methyl gallate and (+)-catechin, of which only the amentoflavone exhibited positive mutagenicity to TA98 (+S9, -S9). (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: Byrsonima crassa; Ames test; mutagenic activity; micronuclei; amentoflavone